Simultaneous Local Heating/Thermometry Based on Plasmonic Magnetochromic Nanoheaters. Issue 24 (14th May 2018) - Li, Zhi; Lopez‐Ortega, Alberto; Aranda‐Ramos, Antonio; Tajada, José Luis; Sort, Jordi; Nogues, Carme; Vavassori, Paolo; Nogues, Josep; Sepulveda, Borja
Abstract: A crucial challenge in nanotherapies is achieving accurate and real‐time control of the therapeutic action, which is particularly relevant in local thermal therapies to minimize healthy tissue damage and necrotic cell deaths. Here, a nanoheater/thermometry concept is presented based on magnetoplasmonic (Co/Au or Fe/Au) nanodomes that merge exceptionally efficient plasmonic heating and simultaneous highly sensitive detection of the temperature variations. The temperature detection is based on precise optical monitoring of the magnetic‐induced rotation of the nanodomes in solution. It is shown that the phase lag between the optical signal and the driving magnetic field can be used to detect viscosity variations around the nanodomes with unprecedented accuracy (detection limit 0.0016 mPa s, i.e., 60‐fold smaller than state‐of‐the‐art plasmonic nanorheometers). This feature is exploited to monitor the viscosity reduction induced by optical heating in real‐time, even in highly inhomogeneous cell dispersions. The magnetochromic nanoheater/thermometers show higher optical stability, much higher heating efficiency and similar temperature detection limits (0.05 °C) compared to state‐of‐the art luminescent nanothermometers. The technological interest is also boosted by the simpler and lower cost temperature detection system, and the cost effectiveness and scalability of the nanofabrication process, thereby highlighting the biomedical potential of this nanotechnology. Abstract : Magnetoplasmonic nanodomes (a, b) provide unique control in photothermal therapies by merging local simultaneous plasmonic heating and innovative magnetochromic thermometry. Nanodomes magnetic rotation under weak alternating magnetic induction B (c) generates an intense transmittance τ modulation (d). Analysis of the phase lag Δφ between B and τ (d, e) enables real‐time and accurate quantification of the optically induced temperature variation.